Long-Term Patient-Reported Outcomes of Visual Field Defects and Compensatory Mechanisms in Patients After Cerebral Hemispherectomy. Issue 2 (June 2021) - Meer, Elana A.; Chen, Monica F.; Jones, Monika; Mathern, Gary W.; Pineles, Stacy L.
Abstract : Background: In cases of intractable epilepsy resistant to drug therapy, hemispherectomy is often the only treatment option to mitigate seizures; however, the true long-term subjective visual outcomes are relatively unexplored. In this study, we sought to determine and characterize patient-reported visual function years after hemispherectomy. Methods: This was an observational study conducted on a large cohort of children with seizure disorder treated with cerebral hemispherectomy. An online survey was sent to parents with questions to assess subjective visual function with a variety of questions from presence of visual field defects after hemispherectomy, to improvement over time, compensatory mechanisms used, and development of strabismus. Results: This survey was emailed to 248 parents of previously evaluated children who agreed to be re-surveyed, 48 (20%) of which responded. The average age at hemispherectomy was approximately 5 (±4) years, and the average time after hemispherectomy was 7 (±5) years. Thirty-nine patients (81%) were seizure-free after 1 surgery and 85% (n = 41) were seizure-free after ≥1 surgeries. Thirty-four (71%) experienced a visual field defect after surgery, but 25 (52%) experienced subjective improvement over time. Thirty-eight (79%) used compensatory mechanisms, such as head tilting, with 16 (33%) patients experiencing subjective improvement over time. Twenty-seven (56%) patients experienced a decrease in visual acuity after surgery with 12 (25%) experiencing subjective improvement over time. Conclusion: In a large cohort examining patient-reported visual outcomes years after hemispherectomy, most patients experienced strabismus and/or visual field defects. However, more than half reported improvements and compensatory mechanisms (exotropic strabismus and ipsilateral esotropic strabismus) over time, presumably to enhance visual field function. By exploring subjective visual and cognitive function, this paper uniquely characterizes patient-reported improvements over time, and provides motivation for larger longitudinal studies using more quantitative measures of visual function and improvement after hemispherectomy. Abstract : Supplemental Digital Content is Available in the Text.